Larangan Impor Pakaian Bekas - Sinmiasa, Tirza Christin Luciana; Balik, Agustina (KANJOLI Business Law Review, 2025)
Clothing is a basic human need that serves not only a physical function but also carries psychological and social dimensions reflected in the phenomena of fashion and brands as symbols of status. The import of branded used clothes in the context of globalization is a trend in Indonesia because of its more affordable prices. However, since the issuance of the Minister of Trade Regulation Number 51/M-DAG/PER/7/2015, the import of used clothing has been prohibited in order to protect the national textile industry and prevent the spread of diseases. This study aims to analyze the import procedures based on the Minister of Trade Regulation Number 40 of 2022 concerning Prohibited Export Goods and Prohibited Import Goods, as well as to examine the legal consequences for importers who distribute secondhand clothing to business actors. The research method employed is normative legal research with a descriptive-analytical approach. The results show that the regulation serves as an important instrument for controlling the flow of imported goods, particularly secondhand items, as a form of the government’s commitment to protecting national interests, maintaining economic growth, and ensuring environmental safety and sustainability. Importers are required to comply with the applicable legal provisions and quality standards. Violations of the prohibition on importing used clothing may result in imprisonment of up to five years and/or a maximum fine of five billion rupiahs. Based on the Consumer Protection Law, additional sanctions may include imprisonment of up to five years or fines of up to two billion rupiahs. Law enforcement measures are carried out through the destruction of illegal goods, business termination, and revocation of trade licenses.